In Situ Transformable Nanoparticle Effectively Suppresses Bladder Cancer by Damaging Mitochondria and Blocking Mitochondrial Autophagy Flux - Yulin Lv; Benli Song; Guang Yang; Yuting Wang; Zeyu Wu; Minggui Si; Zongzheng Yang; Huilin Chen; Chen Liu; Min Li; Yinshi Zhang; Zengying Qiao; et al. (Advanced Science)
Abstract Tumor therapeutic strategies based on mitochondrial damage have become an emerging trend. However, the low drug delivery efficiency caused by lysosomal sequestration and the activation of protective mitochondrial autophagy severely restricts the therapeutic efficacy. Herein, an in situ transformable nanoparticle named KCKT is developed to promote lysosomal escape and directly damage mitochondria while blocking mitochondrial autophagy. KCKT exhibits acid responsiveness for precise self‐assembly into nanofibers within the lysosomes of cancer cells. The massive accumulation of nanofibers and excessive production of reactive oxygen species (ROS) under sonodynamic therapy synergistically induce lysosomal damage. This facilitates the escape of nanofibers from lysosomal sequestration, thereby enhancing drug delivery. Subsequently, the escaped nanofibers specifically aggregate around the mitochondria for long‐term retention and generate ROS under ultrasound irradiation to induce mitochondrial damage. Notably, due to lysosomal dysfunction, damaged mitochondria cannot be cleared by autophagy, further aggravating oxidative damage. These results reveal that KCKT effectively improves drug delivery and mitochondria‐targeted therapy efficiency by blocking protective autophagy. These findings hold significant potential for advancing the field of mitochondria‐targeted therapy.